Effects of different climatic and soil factors at different locations on chemical composition of bush tea (Athrixia phylicoides DC.) - Nchabeleng, Lehlohonolo (University of Limpopo (Turfloop Campus), 2012)
Refer to document
Thesis (M.Sc. (Horticulture)) --University of Limpopo, 2012
Keywords: Bush tea (Athrixia phylicoides DC); 633.7242; Herbal teas; Medicinal plants -- South Africa; Tea -- South Africa -- Limpopo